炎症标志物动态变化对急性缺血性卒中患者血管内治疗预后的影响 Effects of Dynamic Changes of Inflammatory Markers on Prognosis of Patients with Acute Ischemic Stroke Undergoing Endovascular Treatment - 王辰涛，戴婧，李瑛姿，温宇昕，董理，刘春风，刘慧慧(WANG Chentao, DAI Jing, LI Yingzi, WEN Yuxin, DONG Li, LIU Chunfeng, LIU Huihui ) (Zhongguo cuzhong zazhi)
目的 探讨急性大血管闭塞性缺血性卒中（acute ischemic stroke with large vessel occlusion，LVO-AIS）患者血管内治疗（endovascular treatment，EVT）术前、术后24 h炎症标志物水平及其动态变化与3个月预后的关系。 方法 回顾性连续纳入2017年4月—2021年10月在苏州大学附属第二医院接受EVT的LVO-AIS患者，根据术后3个月mRS评分分为预后良好（mRS评分0～2分）组与预后不良（mRS评分3～6分）组。收集两组患者的年龄、性别、既往史、术前与术后24 h炎症反应相关指标[中性粒细胞（neutrophil，NEUT）、中性粒细胞与淋巴细胞比值（neutrophil to lymphocyte ratio，NLR）、全身性炎症反应指数（systemic inflammation response index，SIRI）等]资料。通过logistic回归分析探讨炎症标志物与患者不良预后、症状性颅内出血（symptomatic intracranial hemorrhage，sICH）的相关性。 结果 共纳入354例LVO-AIS患者，其中预后良好组120例（33.90%），预后不良组234例（66.10%）。多因素logistic回归分析显示，EVT术后24 h NEUT（OR 1.24，95%CI 1.12～1.37，P<0.001）、NLR（OR 1.09，95%CI 1.03～1.14，P=0.001）、SIRI（OR 1.14，95%CI 1.05～1.23，P=0.002）是3个月不良预后的独立危险因素。EVT术后24 h NEUT（OR 1.23，95%CI 1.11～1.36，P<0.001）、NLR（OR 1.06，95%CI 1.03～1.10，P<0.001）、SIRI（OR 1.08，95%CI 1.02～1.14，P=0.005）是患者发生sICH的独立危险因素。 结论 术后炎症标志物NEUT、NLR、SIRI的动态升高可能增加LVO-AIS患者EVT后3个月不良预后的风险。 Abstract: Objective To explore the relationship between the levels of inflammatory markers before and 24 hours after endovascular treatment (EVT) in patients with acute ischemic stroke with large vessel occlusion (LVO-AIS) and their dynamic changes with prognosis at 3 months. Methods This retrospective study included patients with LVO-AIS who underwent EVT at the Second Affiliated Hospital of Soochow University between April 2017 and October 2021. Based on the mRS score at 3 months post-EVT, patients were divided into two groups: the favorable prognosis group (mRS score 0-2 points) and the poor prognosis group (mRS score 3-6 points). Data on age, sex, past history, and preoperative and postoperative 24 hours inflammatory response indicators [such as neutrophil (NEUT), neutrophil to lymphocyte ratio (NLR), and systemic inflammation response index (SIRI)] were collected for both groups. The association between inflammatory markers and poor prognosis, as well as the occurrence of symptomatic intracerebral hemorrhage (sICH) was explored through logistic regression analysis. Results A total of 354 patients with LVO-AIS were included in this study, with 120 (33.90%) in the favorable prognosis group and 234 (66.10%) in the poor prognosis group. Multivariable logistic regression analysis revealed that NEUT (OR 1.24, 95%CI 1.12-1.37, P<0.001), NLR (OR 1.09, 95%CI 1.03-1.14, P=0.001), and SIRI (OR 1.14, 95%CI 1.05-1.23, P=0.002) levels 24 hours after EVT were independent risk factors for poor prognosis at 3 months. NEUT (OR 1.23, 95%CI 1.11-1.36, P<0.001), NLR (OR 1.06, 95%CI 1.03-1.10, P<0.001), SIRI (OR 1.08, 95%CI 1.02-1.14, P=0.005) levels 24 hours after EVT were independent risk factors for the occurrence of sICH in patients. Conclusions The dynamic elevation of postoperative inflammatory markers NEUT, NLR, and SIRI levels may increase the risk of poor prognosis at 3 months after EVT in patients with LVO-AIS.